2008
DOI: 10.1111/j.1743-6109.2007.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

How Urologists Manage Erectile Dysfunction after Radical Prostatectomy: A National Survey (REPAIR) by the French Urological Association

Abstract: Introduction There is little sound information on how urologists manage erectile dysfunction (ED) arising after radical prostatectomy (RP) in a real-world situation. Aim To perform a national survey of how French urologists manage ED after RP in routine practice. Main Outcome Measures Choice of first-line treatment, type of treatment (rehabilitation of erecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 28 publications
1
47
0
Order By: Relevance
“…55,[63][64][65] Currently, PR methods include the use of PDE 5 I, intracavernosal self-injection/intraurethral suppositories, VED or a combination of different therapy modalities. 55,[63][64][65] Pathophysiology Erectile function (EF) becomes impaired immediately after RP secondary to cavernous nerve damage during surgery, resulting in neuropraxia. 66 Even with the most meticulous nerve-sparing dissection, some degree of neuropraxia is unavoidable because of the close proximity of the nerves to the prostatic gland.…”
Section: 48-52mentioning
confidence: 99%
“…55,[63][64][65] Currently, PR methods include the use of PDE 5 I, intracavernosal self-injection/intraurethral suppositories, VED or a combination of different therapy modalities. 55,[63][64][65] Pathophysiology Erectile function (EF) becomes impaired immediately after RP secondary to cavernous nerve damage during surgery, resulting in neuropraxia. 66 Even with the most meticulous nerve-sparing dissection, some degree of neuropraxia is unavoidable because of the close proximity of the nerves to the prostatic gland.…”
Section: 48-52mentioning
confidence: 99%
“…Even so, according to a recent survey in France, only 38% of urologists routinely offer some form of pharmacological penile rehabilitation after RP, whereas 87% of the International Society for Sexual Medicine practitioners do so, with those managing over 50 RP patients per year being the most proactive. 3,4 In addition, even if erections are restored after RP, with or without treatment, sexual bother increases after RP and sexual health most often does not return to its preoperative level. 5 The aim of this study is to assess the impact of RP on patients' sexual health and satisfaction according to sexual motivation.…”
Section: Introductionmentioning
confidence: 99%
“…7,15 Despite this ongoing controversy, supportive evidence from animal studies continues to emerge, 16 and there is evidence that penile rehabilitation is widely used in everyday clinical practice. 17 Giuliano et al 18 explored practice patterns of French urologists and found that 488% used some form of early therapy after RRP, such as regular intracavernous injection (ICI) for rehabilitation (39%), ICI on demand for intercourse (30%), PDE5-Is on demand (16%) or regular PDE5-Is for rehabilitation (8%), alternating ICI and PDE5-Is (7%) and vacuum devices (o1%).…”
Section: Introductionmentioning
confidence: 99%